Pengaruh Beban Pajak Tangguhan Terhadap Persistensi Laba, Penghindaran Pajak Dan Nilai Perusahaan - Prastyatini, Sri Lestari Yuli; Candra, Yogi Karuna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the impact of deferred tax expense on earnings persistence, tax avoidance, and firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2018–2022. A purposive sampling method was used to select samples from a population of 87 companies. Linear regression analysis was employed to analyze the data. The study shows that deferred tax expense has a positive and significant effect on earnings persistence with a t-value of 2.422, significance of 0.022, and R² of 0.173, and on firm value with a t-value of 6.653, significance of 0.000, and R² of 0.496, but has no effect on tax avoidance with a t-value of 1.479, significance of 0.153, and R² of 0.090.. This study is expected to serve as a reference for formulating more effective strategies in managing deferred tax expenses to enhance earnings persistence and firm value.